Accelerating the Association of the Most Stable Protein–Ligand Complex by More than Two Orders of Magnitude. (28th June 2016) - Giese, Christoph; Eras, Jonathan; Kern, Anne; Schärer, Martin A.; Capitani, Guido; Glockshuber, Rudi
Abstract: The complex between the bacterial type 1 pilus subunit FimG and the peptide corresponding to the N‐terminal extension (termed donor strand, Ds) of the partner subunit FimF (DsF) shows the strongest reported noncovalent molecular interaction, with a dissociation constant ( K D ) of 1.5×10 −20  m . However, the complex only exhibits a slow association rate of 330 m −1  s −1 that limits technical applications, such as its use in affinity purification. Herein, a structure‐based approach was used to design pairs of FimGt (a FimG variant lacking its own N‐terminal extension) and DsF variants with enhanced electrostatic surface complementarity. Association of the best mutant FimGt/DsF pairs was accelerated by more than two orders of magnitude, while the dissociation rates and 3D structures of the improved complexes remained essentially unperturbed. A K D  value of 8.8×10 −22  m was obtained for the best mutant complex, which is the lowest value reported to date for a protein/ligand complex.